Study of the Prevalence and Determinants of Stunting Based on SSGI 2024 Data in East Kalimantan - Dewi Saptowati; Anindya Monika Putri; Morrin Choirunnisa Thohira; Rifdah Wardani (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Stunting remains one of the major public health issues in Indonesia, particularly among children under five. The decline in stunting prevalence nationally shows a positive trend, but challenges remain at the regional level, including in East Kalimantan. Objective : This study aims to analyze trends in stunting prevalence and its determinants in East Kalimantan, using data from the 2024 Indonesian Nutritional Status Survey (SSGI), to inform regional policy interventions. Research Methods/ Implementation Methods : The method used is a descriptive, quantitative approach with a comparative analysis of national data Results : The results indicate that all districts/cities in East Kalimantan reported stunting prevalence rates above the national average in 2024, except for Kutai Kartanegara. Factors such as the high incidence of closely spaced pregnancies, low participation in prenatal classes, the proportion of babies born with low birth weight and short birth length (LBW and SBL), the quality of complementary feeding (MPASI), low consumption of iron tablets among pregnant women, limited coverage of vitamin A supplementation, low public awareness about stunting, suboptimal performance of family assistance teams, adequate sanitation and drinking water are believed to contribute to the high prevalence in East Kalimantan. Conclusion/Lesson Learned : These findings underscore the importance of sustainable, specific, and sensitive nutrition interventions, as well as a multisectoral approach involving families and communities. This study is expected to serve as a reference for local governments in developing evidence-based policies to accelerate stunting reduction in East Kalimantan.